Table of Content - -, (Journal of medical and pharmaceutical sciences, 2024)
Table of Content:1. Hereditary blood diseases in Jeddah (Sickle Cell Anemia – Thalassemia)Amna Sami Jamal Al-Lail, Nadia Rafed Al-Obaidi2. Medical Students’ Perceptions of Online Learning During the COVID-19 Pandemic, Kuwait University: A National SurveyAmar Ali Alnaqi, Ali Jasim Buabbas, Nada Jalal Jaafar, Aminah Mohammed Alawadi, Hamza Mohammed Alshawaf3. Ovarian Torsion in Pregnancy: A Case ReportYasmeen Hassan Albadrani
Keywords: Journal of Medical and Pharmaceutical Sciences